PEER MENTORING: A PROPOSED MODEL TO IMPROVE THE ENGLISH STUDENTS’ SPEAKING ABILITY AT IAIN TULUNGAGUNG - Muh. Basuni (Jurnal Bahasa Lingua Scientia, 2014)
In business and human resource management, mentoring has been acknowledged as an effective way to develop career and achievement. This may be true to English teaching. Mentoring can be used as an alternative strategy to help students improve their language proficiency.   English Department of IAIN Tulungagung possesses unique characteristic since it is a non-Islamic study which is run by an Islamic institute. Its unique characteristic lies on the number of the Islamic content courses, of which proportion is much bigger comparing to the same kinds of department which is run by non-Islamic universities. This causes to the less credit of English skill and content courses offered to the students. To meet the students’ need of a good proficiency at English skills, especially speaking, any effort must be conducted. One of the proposed alternatives is conducting a peer mentoring. This article proposes and discusses a model of peer mentoring program to improve the English students’ speaking ability. The peer mentoring model is selected since it gives fruitful benefits to the junior students as the mentees, the senior students as the mentors, and the faculty members or the English department lecturers as the supervisors.